INDEKS KEPUASAN MASYARAKAT ELECTRONIC SERVICE QUALITY PADA APLIKASI LAPAK PROBOLINGGO DI KANTOR KELURAHAN SIDOMUKTI KECAMATAN KRAKSAAN - Siti Marwiyah; Verto Septiandika; Murtias Puji Astutik (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine internet-based services at the Sidomukti Village Office, Kraksaan District, Probolinggo Regency as measured using the Community Satisfaction Index. Data collection techniques were carried out by means of observation, questionnaires, interviews and documentation. The data analysis method uses simple regression analysis using quantitative descriptive research methods with a phenomenological approach. From the results of the study, it can be seen that the Community Satisfaction Index (IKM) for services at the Sidomukti Sub-District Office, Kraksaan District is 2.91 with a conversion rate of 72.75 which can be declared